2005
DOI: 10.1038/sj.sc.3101763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indomethacin on motor activity and spinal cord free fatty acid content after experimental spinal cord injury in rabbits

Abstract: Study design: Determination of functional and biochemical parameters as well as the effect of specific therapies on these parameters, in the experimental model of neurotrauma in rabbits. Objective: To assess the effect of indomethacin (0.1-3.0 mg/kg for 9 days), a potent inhibitor of endogenous prostaglandin synthesis, on the motor activity and on the spinal cord tissue concentration of free palmitic, stearic, oleic, arachidonic and docosahexaenoic acids in an experimental model of a spinal cord injury in rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
15
1
Order By: Relevance
“…The species resulting from the hydrolysis of phospholipids, due to the production of enzyme PLA 2 during the SCI, can still be detected in the samples one week after the injury. This result slightly differs from the literature where the increase of FFAs and DG is followed by a decline around 10h after the SCI, even if time points later than 24h were not studied 69, 70, 73, 74. However, a recent MALDI mass spectrometry imaging study has revealed the production of lysophosphatidylcholine in the injured ischemic rat brain 48h after the MCA occlusion 95.…”
Section: Resultscontrasting
confidence: 91%
“…The species resulting from the hydrolysis of phospholipids, due to the production of enzyme PLA 2 during the SCI, can still be detected in the samples one week after the injury. This result slightly differs from the literature where the increase of FFAs and DG is followed by a decline around 10h after the SCI, even if time points later than 24h were not studied 69, 70, 73, 74. However, a recent MALDI mass spectrometry imaging study has revealed the production of lysophosphatidylcholine in the injured ischemic rat brain 48h after the MCA occlusion 95.…”
Section: Resultscontrasting
confidence: 91%
“…1a). Interestingly, indomethacin, an NSAID that has been tested in several SCI studies with minimal benefit (Guven et al, 1999;Pantovic et al, 2005;Schwab et al, 2004), does not block Rho signaling in our in vitro studies.…”
Section: Ibuprofen Blocks Rho-mediated Signalingmentioning
confidence: 97%
“…Conversely, no significant changes in the motor score have been observed at 4 weeks after SCI in indomethacin-treated rats after spinal cord compression (Guth et al 1994). In a rabbit model of spinal cord contusion, animals treated daily with indomethacin starting immediately after injury have been reported to have a better motor score function visible from day 1 to the end of the observation at day 9 after SCI (Pantovic et al 2005). These early treatment effects on motor function have not been observed in the rodent trials published for NSAID treatment after SCI.…”
Section: Functional Recoverymentioning
confidence: 99%